2017
DOI: 10.1111/ijd.13799
|View full text |Cite
|
Sign up to set email alerts
|

Bullous pemphigoid complicated by cytomegalovirus disease as a manifestation of immune reconstitution inflammatory syndrome: retrospective analyses of our institutional cases and literature review

Abstract: Frequent WBC, PLT, and ALT measurements may identify BP patients at a risk of subsequently developing CMV disease. Careful monitoring of CMV disease in BP refractory to systemic corticosteroids may reduce the risk of fatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Research published recently pointed out that patients at risk of malnutrition were more likely to have a healthcare-associated infection, with malnutrition assessed by BMI, recent weight loss, and dietary intake (25). A case report and retrospective analysis from Japan discovered that higher BP180 antibody titer resistant to corticosteroids treatment was a risk factor for developing CMV infection in BP patients (26). The infection by Varicella Zoster virus (VSV) that also belongs to the family of herpes virus as CMV was reported to enhance BP180 antibody production (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research published recently pointed out that patients at risk of malnutrition were more likely to have a healthcare-associated infection, with malnutrition assessed by BMI, recent weight loss, and dietary intake (25). A case report and retrospective analysis from Japan discovered that higher BP180 antibody titer resistant to corticosteroids treatment was a risk factor for developing CMV infection in BP patients (26). The infection by Varicella Zoster virus (VSV) that also belongs to the family of herpes virus as CMV was reported to enhance BP180 antibody production (27).…”
Section: Discussionmentioning
confidence: 99%
“…The infection by Varicella Zoster virus (VSV) that also belongs to the family of herpes virus as CMV was reported to enhance BP180 antibody production (27). Additionally, reduction in serum WBC, PLT, and increase in ALT have also been reported to be risk factors (26).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the timing of withdrawal or tapering of immunosuppressive agents (prednisolone) may be critical in determining whether AHA will develop in patients with BP. Thus immune recovery that occurs shortly after withdrawal or tapering of prednisolone doses might have a strong impact on the subsequent development of AHA ( 9 ). In this regard, given that DPP-4 is also known as a T-cell activation antigen, CD26, and is highly expressed on activated T cells, particularly Th1 and Th17 cells ( 10 ), it is likely that patients treated with DPP-4is could be in an immunosuppressive state.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that CMV-IRIS develops 3 to 4 days after tapering corticosteroids in severe drug eruptions and bullous pemphigoid. 4,8,9 When patients have an apparent flare that cannot be explained by an increase in inflammatory parameters and RA symptoms, CMV-IRIS should be suspected, and a more thorough clinical evaluation of CMV reactivation should be done immediately. To identify CMV reactivation, repetitive diagnostic measures with taking of tissue samples and CMV-specific immunohistochemical staining of the tissue samples are necessary.…”
Section: Discussionmentioning
confidence: 99%